What factors influence physiotherapy service provision in rural communities? A pilot study. (June 2014) - Adams, Robyn; Sheppard, Lorraine; Jones, Anne; Lefmann, Sophie
Abstract Objective To obtain stakeholder perspectives on factors influencing rural physiotherapy service provision and insights into decision making about service provision. Design Purposive sampling, open‐ended survey questions and semi‐structured interviews were used in this exploratory, qualitative study. Setting A rural centre and its regional referral centre formed the pilot sites. Participants Nine participant perspectives were obtained on rural physiotherapy services. Main outcome measures Stakeholder perspectives on factors influencing rural physiotherapy service provision and service level decision making. Results Workforce capacity and capability, decision maker's knowledge of the role and scope of physiotherapy, consideration of physiotherapy within resource allocation decisions and proof of practice emerged as key issues. The latter three were particularly reflected in public sector participant comments. Business models and market size were identified factors in influencing private practice. Conclusion Influencing factors described by participants both align and extend our understanding of issues described in the rural physiotherapy literature. Participant insights add depth and meaning to quantitative data by revealing impacts on local service provision. Available funding and facility priorities were key determinants of public sector physiotherapy service provision, with market size and business model appearing more influential in private practice. The level of self direction or choice about which services to provide, emerged as a point of difference between public and private providers. Decisions by public sector physiotherapists about service provision appear constrained by existing capacity and workload. Further research into service level decision making might provide valuable insights into rural health service delivery.